DNA triplex formation with 5-dimethylaminopropargyl deoxyuridine. - Rusling, D; Peng, G; Srinivasan, N; Fox, K; Brown, T (2009)
We have prepared triplex-forming oligonucleotides containing the nucleotide analogue 5-dimethylaminopropargyl deoxyuridine (DMAPdU) in place of thymidine and examined their ability to form intermolecular triple helices by thermal melting and DNase I footprinting studies. The results were compared with those for oligonucleotides containing 5-aminopropargyl-dU (APdU), 5-guanidinopropargyl-dU (GPdU) and 5-propynyl dU (PdU). We find that DMAPdU enhances triplex stability relative to T, though slightly less than the other analogues that bear positive charges (T << PdU < DMAPdU < APdU < GPdU). For oligonucleotides that contain multiple substitutions with DMAPdU dispersed residues are more effective than clustered combinations. DMAPdU will be especially useful as a nucleotide analogue as, unlike APdU and GPdU, the base does not require protection during oligonucleotide synthesis and it can therefore be used with other derivatives that require mild deprotection conditions.